Poglądy Aleksandra Wielopolskiego i jego kręgu politycznego na sprawę reform chłopskich w XIX wieku w Królestwie Polskim (do 1862 r.) - Ćwikła, Adam (PRAWO i WIĘŹ, 2025)
Aleksander Wielopolski (1803–1877) was one of the key political activists in the Kingdom of Poland in the 1860s. His ideological platform was based on the concept of loyalty to the Russian Empire and the pursuit of a conciliatory policy towards the partitioning powers. Serving as head of the Civil Government in 1862–1863, he attempted to implement modernizing reforms in the Kingdom, believing that only cooperation with the tsar offered a real opportunity to improve the situation of Polish society. Aleksander Wielopolski saw resolving the peasant question as one of the key conditions for stabilizing social relations and the sustainable development of the Kingdom of Poland. He advocated the enfranchisement of peasants, but in an evolutionary and moderate form, respecting the interests of the landed gentry. He advocated granting peasants land ownership while providing compensation to landowners, opposing radical revolutionary solutions. In 1861–1862, he initiated partial reforms, including the abolition of personal serfdom, the reduction of serfdom payments, and the possibility of converting them into rent. Although his program assumed a gradual transformation of the agrarian structure, it was not fully implemented due to the outbreak of the January Uprising in 1863. The final enfranchisement reform in the Kingdom was carried out by the Russian authorities in 1864, using it as a tool to weaken the social base of the national movement.